Neonatal diabetes mellitus due to a new KCNJ11 mutation - 10 years of the patient`s follow-up - Ješić, Maja D; Stock, Helena; Zdravković, Vera; Kovačević, Smiljka; Savić, Marko; Ješić, Miloš M (The Turkish Journal of Pediatrics, 2021)
Background. Mutations in the KCNJ11 gene, which encodes the Kir6.2 subunit of the ATP-sensitive potassium channel, often result in neonatal diabetes. Case. In this report, we describe a 10-year-old girl who is heterozygous for a new missense mutation in the KCNJ11 gene and whose treatment was successfully switched from insulin to sulfonylurea (glibenclamide) therapy when she was one month old. 10-year data on a low-dose of glibenclamide monotherapy showed excellent glycaemic control with no reports of severe hypoglycaemia and microvascular complications. Conclusion. An early genetic diagnosis of neonatal diabetes mellitus is highly beneficial because early switch from insulin to sulfonylurea is safe, avoids unnecessary insulin therapy and promotes sustained improvement of glycaemic control on long-term follow-up.
Keywords: neonatal diabetes mellitus; new KCNJ11 mutation; sulfonylurea therapy